Utilization of Instagram Social Media as Publication and Information Media at the State Assets and Auction Service Office (KPKNL) Yogyakarta - Gusti, Jhelisa Mutiara; Andryani, Kristina; Saputri, Dhea Octavia (PT FORMOSA CENDEKIA GLOBAL, 2025)
The formulation of the problem of this research is, how to use Instagram social media as a medium for publication and information at the KPKNL Yogyakarta office. The aim of this research is to determine the use of Instagram social media for publication and information media at KPKNL Yogyakarta. Review of the theory used, namely New Media which uses the concept of The Circular Model of SOME, Regina Lutterll's theory. This research uses a descriptive qualitative research approach with observation, interview and documentation data collection methods. The findings and results of thisresearch are that KPKNL Yogyakarta chosethe social media Instagram based on the increasing use of social media and in accordance with the target. Before posting content, a schedule was made.